Physiological and metabolic characteristics of elite tug of war athletes. Issue 6 (1st December 2001) - Warrington, G; Ryan, C; Murray, F; Duffy, P; Kirwan, J P
Abstract : Objective —To determine the aerobic power (V̇o 2 max ), body composition, strength, muscular power, flexibility, and biochemical profile of an elite international squad of tug of war athletes. Methods —Sixteen male competitors (mean (SEM) age 34 (2) years) were evaluated in a laboratory. For comparative purposes, data were analysed relative to normative data for our centre and to a group of 20 rugby forwards from the Irish international squad. Results —The tug of war participants were lighter (83.6 (3.0) v 104.4 (1.8) kg, p<0.0001) and had less lean body mass (69.4 (2.1) v 86.2 (1.2) kg) than the rugby players and had lower than normal body fat (16.7 (0.9)%); all values are mean (SEM). Aerobic power measured during a treadmill test was 55.8 (1.6) ml/kg/min for the tug of war participants compared with 51.1 (1.4) ml/kg/min for the rugby forwards (p<0.03). A composite measure of strength derived from (sum of dominant and non-dominant grip strength and back strength)/lean body mass yielded a strength/mass ratio that was 32% greater (p<0.0001) for the tug of war group than the rugby group. Dynamic leg power was lower for the tug of war group than the rugby forwards (4659.8 (151.6) v 6198.2 (105) W respectively; p<0.0001). Leg flexibility was 25.4 (2.0) cm for the tug of war group. Back flexibility was 28.6 (1.4) cm which was lower (p<0.02) than the rugby forwards 34.2 (1.5) cm. Whereas blood chemistry and haematology were normal, packed cell volume, haemoglobin concentration, and erythrocyte volume were lower in the tug of war group than in the rugby players (p<0.05). All three haematological measures correlated with muscle mass (packed cell volume, r 2 = 0.37, p<0.0001; haemoglobin concentration, r 2 = 0.13, p<0.05; erythrocyte volume, r 2 = 0.21, p<0.01). Conclusions —The data indicate that international level tug of war participants have excellent strength and above average endurance relative to body size, but have relatively low explosive leg power and back flexibility. The data provide reference standards for the sport and may be useful for monitoring and evaluating current and future participants.